Pengaruh Kurs Rupiah Terhadap Ihsg Di Index Stock Exchange (Idx) Maret 2020, Studi Kasus Efek Covid-19 Di Indonesia - Ady Kurnia; Lili Marlinah; Renny Mointi (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
This study aims to determine the effect of Rupiah Exchange Rate Influence on Stock Prices on the March 2020 Stock Exchange Index (IDX), Case Study of Covid-19 Securities in Indonesia. During the covid-19 pandemic it was exposed in Indonesia. This type of research is quantitative research that is descriptive. The variables of this study are: the exchange rate variable is IDR (X) and the dependent variable is IHSG (Y). The data used in this study are secondary data, the source of historical IHSG data after the announcement of the official Covid-19 infection in Indonesia on 3 March 2020 to 31 March 2020. The results of the study found that there was a significant relationship between the Rupiah Exchange Rate and the Jakarta Composite Index. This study shows that the weakening of the Rupiah against the US Dollar (or the dollar is very expensive against the rupiah), the Composite Stock Price Index (IHSG) also weakened, during March when the COVID-19 Virus pandemic was still endemic.